Pemahaman Hadis tentang Kewajiban Wudu: (Telaah Metode Ijmali Kitab Syarh as-Suyuthi ‘ala Sunan an-Nasa’i) - Muhid, Muhid; Pratiwi, Hani (Prodi Ilmu Hadis Fakultas Ushuluddin dan Dakwah Institut Agama Islam Negeri Madura, 2024)
The science of hadith sharia is the study of the meaning or explanation contained in a hadith. In studying a hadith, there are several supporting sciences involved, one of which is the science of hadith sharia. When studying the science of hadith sharia, one will also learn about the methods used to explain a hadith. These methods are what help scholars to explain hadiths that are not yet fully understood by readers. Some of the methods used to explain hadiths are the analytical, ijmali, and muqarrin methods. This paper will focus more on the ijmali method used to explain hadiths. The data in this study was obtained from library research sources. The purpose of this study is to understand what the ijmali method is and to understand the hadith sharia about the obligation of wudu for every prayer in one of the hadith sharia books that uses the ijmali method in its explanation.